SPE Symposium on Improved Oil Recovery 2008
DOI: 10.2118/112976-ms
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Rate of Clean Up for Oil Zones after a Gel Treatment

Abstract: In our previous work, X-ray computed microtomography (XMT) was used to establish why pore-filling Cr(III)-acetate-HPAM gels reduced permeability to water much more than to oil. Our results suggest that permeability to water was reduced to low values because water must flow through gel itself, whereas oil pressing on the gel in a porous medium forced pathways by dehydration-leading to relatively high permeability to oil. Those studies involved obtaining 3D pore-level Xray images at the saturation endpoints-for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…5). The rate of increase in oil permeability was roughly the same for the two porous media (Seright et al 2008). The rapid jump in oil saturation in Berea between 0 and 0.1 PV may have occurred simply because the oil finger fortuitously swept the imaged volume.…”
Section: Imbibition and Drainage As A Function Of Throughput After Gementioning
confidence: 76%
See 3 more Smart Citations
“…5). The rate of increase in oil permeability was roughly the same for the two porous media (Seright et al 2008). The rapid jump in oil saturation in Berea between 0 and 0.1 PV may have occurred simply because the oil finger fortuitously swept the imaged volume.…”
Section: Imbibition and Drainage As A Function Of Throughput After Gementioning
confidence: 76%
“…Wettability tests produced Amott-Harvey indexes of 0.7 for the brine (1% NaCl, 0.1% CaCl 2 )/oil (hexadecane)/Berea sandstone system and −0.8 for the brine/oil/porous polyethylene system-confirming the water-wet character of Berea sandstone and the hydrophobic character of porous polyethylene. On the basis of XMT analysis, the two porous media have very similar pore size distributions (Seright et al 2006(Seright et al , 2008. Table 1 summarizes the core properties (Seright et al 2002(Seright et al , 2006Prodanovic et al 2006Prodanovic et al , 2007.…”
Section: Core Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For production treatments, such as RPM, it has been observed that the time to restore the oil production can be substantial (Seright 2008). The clean up time can be derived using fractional flow theory and the modified oil and water permeabilities.…”
Section: Clean Up Timementioning
confidence: 99%